Defining transport logistics: a literature review and practitioner opinion based approach - Topolšek, Darja; Čižiūnienė, Kristina; Cvahte Ojsteršek, Tina (Transport, 2018)
There are many concepts in the transport and logistics business: transport, logistics, transportation, forwarding, etc. There are also a number of different study programs and disciplines such as: transport economics, transport logistics, logistics management, etc. All of these titles are often related to the content of the plan, planning, organization, management and control of the movement of human, material, informational and financial flows. However, in practice, they are often correlated and misused. Therefore, it is an important task to properly define these concepts. This article, based on various scientific literature, deals with the concept of transport logistics in various disciplines and fields of research. The results of this analysis made it possible to identify that there is no unified logistic term. Therefore, a qualitative study was also used. The purpose of this study is to identify the concept of transport/logistics companies in the Baltic States as the concept is treated in business. The results of the research have shown that the concept of transport logistics is also understood differently. Therefore, the purpose of this article is to formulate the definition of transport logistics on the basis of the results of the scientific literature analysis and qualitative research.